Studi Pengetahuan Pasien Hipertensi Terhadap Manfaat dan Risiko Obat Herbal sebagai Terapi Pendamping di Puskesmas Kebondalem Kecamatan Pemalang Kabupaten Pemalang - Davina Afra Azizah; Nila Oktaviani (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Hypertension is one of the chronic diseases suffered by many people in Indonesia, including in the Kebondalem Health Center area, Pemalang District. In its treatment, some patients choose to use herbal medicine as a complementary therapy in addition to medical treatment. However, patients' understanding of the benefits and risks of using herbal medicine is still not fully known. Objective: This study aims to examine the level of knowledge of hypertensive patients regarding the benefits and risks of using herbal medicine as a complementary therapy at the Kebondalem Health Center, Pemalang District. Method: This study uses a descriptive method with a quantitative approach. The research sample was hypertensive patients who visited the Kebondalem Health Center and met the inclusion criteria. Data were collected through a validated closed questionnaire, then analyzed descriptively. Results: The results showed that most patients had a moderate level of knowledge regarding the benefits of herbal medicine, but were still low in understanding the risks that might arise from using it simultaneously with medical drugs. Some patients also still believe in myths related to herbal medicine without a strong scientific basis.